A facile method to evaluate the quality of Platycodon grandiflorum A. De Candolle using reference standard extract. (October 2016) - Zeng, Lingfeng; Kong, Huijuan; Zhu, Ming; Yan, Weidong
Highlights: Reference standard extract was used to assess quality of functional food. The main components in reference standard extract were standardized. Batches of Platycodi Radix were evaluated by the reference standard extract method. The results characterized by this method were compared with that characterized by conventional method. Abstract: Platycodi Radix, the root of Platycodon grandiflorum A. De Candolle, is a widely used functional food in East Asia. Reference standard extract, a mixture of marker compounds, is used as a reference substance to quantify platycosides from Platycodi Radix. The convenience and consistency of using reference standard extract as a reference substance was evaluated. The qualitative and quantitative results of platycoside contents in Platycodi Radix characterized by this method were compared with that characterized by the conventional external standards method. The Pearson correlation coefficient test of these two methods was between 0.985 and 0.999. A more comprehensive chemical information including relative retention time, relative peak area and contents of active components were obtained simultaneously from raw material using reference standard extract method. The application of this method may relieve the stress in increasing demands for pure marker compounds.